2023
DOI: 10.1002/smll.202301709
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Self‐Assembly of MXene on Ruthenium Dioxide‐Modified Carbon Cloth for Electrochemical Detection of Kaempferol

Abstract: A superior composite material consisting of MXene and ruthenium dioxide‐modified carbon cloth is synthesized by pulsed laser deposition and electrostatic self‐assembly, which is further utilized to construct a class of novel electrochemical (EC) sensors for kaempferol (KA) detection. The carbon‐cloth‐based electrodes modified by ruthenium dioxide and then MXene are characterized by X‐ray diffraction, scanning electron microscope, and X‐ray photoemission spectroscopy. The EC process on the modified electrodes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It has become one of the major cultivated vegetables in the world and contains rich nutrients. Significant differences in the nutrient composition of different varieties were detected by using high-performance liquid chromatography and electrochemical methods ( Wang et al., 2023 ). Previous studies have shown that S. pimpinellifolium is the ancestor of cultivated tomatoes ( Lin et al., 2014b ), and S. habrochaites is an important wild relative of cultivated tomato, which has a variety of excellent disease resistance and stress resistance traits ( Safari et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has become one of the major cultivated vegetables in the world and contains rich nutrients. Significant differences in the nutrient composition of different varieties were detected by using high-performance liquid chromatography and electrochemical methods ( Wang et al., 2023 ). Previous studies have shown that S. pimpinellifolium is the ancestor of cultivated tomatoes ( Lin et al., 2014b ), and S. habrochaites is an important wild relative of cultivated tomato, which has a variety of excellent disease resistance and stress resistance traits ( Safari et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, glycyrrhetinic acid [ 13 ], platycodon saponin D, beriberiin A, and beriberiin B are reportedly quality markers of Tiedi Wan [ 14 ]. In another development, a novel electro-chemical detector was used for the detection of chemical components in Chinese medicine [ 15 ]. Compared to traditional methods, electrochemical sensors may be another superior option due to their low cost, high sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20–23 ] As an emerging layered inorganic material, 2D MXene with high surface area and excellent electrical conductivity has been successfully employed as an electrode modifier to construct electrochemical sensors to detect biomarkers, environmental pollutants, and drugs. [ 24–28 ] However, owing to the strong tendency of discrete distribution and aggregation of MXene sheets, the MXene‐modified electrode exhibited higher resistance and tremendous loss of surface reactivity, in which the potential of MXene has not been fully exploited. [ 29,30 ] Meanwhile, the weak bonding between the layers of MXene easily leads to the separation in solution, which will reduce the surface availability, reliability, and conductivity of the MXene‐modified electrode.…”
Section: Introductionmentioning
confidence: 99%